Possibility of less radical treatment for patients with early invasive uterine cervical cancer. Issue 7 (14th April 2016) - Kim, Miseon; Ishioka, Shinichi; Endo, Toshiaki; Baba, Tsuyoshi; Mizuuchi, Masahito; Takada, Sakura; Saito, Tsuyoshi
Abstract: Aim: Radical trachelectomy (RT) with lymphadenectomy has become a standard treatment modality for patients with early invasive uterine cervical cancer who hope to preserve fertility. However, pregnancy after RT has high risks of preterm birth. The possibility of more conservative RT and the application of RT for patients with higher clinical stages were studied. Methods: The medical charts and specimens of 42 patients who underwent RT and 64 patients who underwent radical hysterectomy were retrospectively studied. Tumor size, distance between the margin of the cancer and the internal orifice of the uterus (os), parametrial invasion, lymph node metastasis and prognoses were investigated. Results: The average distances between the inner margin of the cancer and the internal os were 37 mm, 29 mm, 18.7 mm and 14 mm for patients with stage 1 A2, 1B1 (≤ 2 cm), 1B1 (> 2 cm) and 1B2, respectively. When amputation was performed 10 mm below the internal os, all 10 patients with 1 A2, 57 with 1B1 (≤ 2 cm), 19 with 1B1 (> 2 cm), and one with 1B2 had a cancer‐free margin > 10 mm. Patients with stage 1 A2 had a cancer‐free margin > 10 mm even if we amputated the cervix 20 mm below the internal os. Parametrial invasion was detected in two patients with stage 1B1. Conclusions: A simple trachelectomy 20 mm below the internal os with pelvic lymphadenectomy might be possible for stage 1 A2 patients. The present method is best for stage 1B1 patients (≤ 2 cm). RT for stage 1B1 (>2 cm) or higher stages should be contraindicated.